Procedural Sedation & Analgesia by Ketamine-Propofol (Ketofol) And Ketamine-Diazepam Combination In Day Case Surgery - A Comparative Study - Kalam, Farzana; Hussain, Pervez Altaf; Ahmed, Masud; Masum, Abdullah (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Introduction: Traditionally Procedural Sedation and Analgesia (PSA) is provided by various drugsand its combinations with mixed effect regarding safety and efficacy. Objective: The aim of the study was to compare the combination of Ketamine & Propofol (Ketofol) andKetamine-Diazepam for PSA in day case surgery. Materials & Methods: This prospective study was carried out in CMH Dhaka on sixty patients equallydivided in two groups between the period of May 2015 to September 2015. Group I patients receivedInjection Ketamine 1mg/kg & Injection Propofol 1mg/kg combination while group II patients receivedInjection Ketamine 2mg/kg & Injection Diazepam 0.2mg/kg combination. Clinical parameters like pulserate, non invasive blood pressure (NIBP), percentage saturation of oxygen (SpO2) were monitored, recordedand analyzed. Recovery was assessed by Aldred Recovery Score (ARS) and compared between groups. Results: Rise of heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP) were statisticallysignificant in group II patients when compared to group I both during the procedure & recovery but riseof mean arterial pressure (MAP) was significant only during procedure. The recovery time in group IIpatients (24.7 ± 3.6 min) was significantly higher (29.7 ± 4.1 min) than group I patients. Side effects likeexcessive bronchial secretion and postoperative agitation were also significantly lesser in Ketofol group. Conclusion: Ketofol provides safer and more effective sedation and analgesia than Ketamine andDiazepam combination. JBSA 2018; 31(2): 75-82